Greenland, view of Kjerulf Fjord through to Dicksons Fjord and Hisinger Gletscher - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. Extreme inner end. In background: L.A.B.'s Scoop Mt. [mountain] shown here on the left, coming from N.E. where it has formed south side of Dickson [Dicksons] Fjord; at this point turns south and forms eastern side of Unknown Valley. Below is Hisinger Glacier [Hisinger Gletscher] in its decline N.E. towards Dickson [Dicksons] Fjord. In foreground; souther [southern] terminal of mts. [mountains] which have formed east side of Kjerulfs [Kjerulf] Fjord. Photo taken from slope of these mts. [mountains] at a point beyond Left Valley, looking S.E. This photo is No. 1 in pan D.